2021
DOI: 10.1002/mgg3.1814
|View full text |Cite
|
Sign up to set email alerts
|

A +3 variant at a donor splice site leads to a skipping of the MYH11 exon 32, a recurrent RNA defect causing Heritable Thoracic Aortic Aneurysm and Dissection and/or Patent Ductus Arteriosus

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Cardiovascular / cerebrovascular manifestation The patient reported no gastrointestinal symptoms suggestive of VM, CIPO, or MMIHS, nor any recurrent fractures, visual disturbances, hypoacusis, stroke, urinary problems, or renal disease, as previously reported in MYH11 mutation carriers (Table 1) [9][10][11][12][13][14][15][16][17][18][19][20]. Whether Parkinson syndrome was due to cerebrovascular involvement or another cause remains controversial.…”
Section: Age (Y) Sex Variant Dosage Phenotype Referencementioning
confidence: 57%
See 3 more Smart Citations
“…Cardiovascular / cerebrovascular manifestation The patient reported no gastrointestinal symptoms suggestive of VM, CIPO, or MMIHS, nor any recurrent fractures, visual disturbances, hypoacusis, stroke, urinary problems, or renal disease, as previously reported in MYH11 mutation carriers (Table 1) [9][10][11][12][13][14][15][16][17][18][19][20]. Whether Parkinson syndrome was due to cerebrovascular involvement or another cause remains controversial.…”
Section: Age (Y) Sex Variant Dosage Phenotype Referencementioning
confidence: 57%
“…The patient is of interest for a novel heterozygous variant of MYH11, which manifested phenotypically as aortic aneurysm, Parkinson syndrome, and noncompaction. Whether the detected heterozygous MYH11 variant was actually responsible for the clinical manifestations remains speculative, but several previous studies reported that heterozygous MYH11 variants can be pathogenic (Table 1) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Except for aortic aneurysm [7,8], the other clinical manifestations of the index patient were not reported in association with MYH11 variants.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…variants in MYH11 result in incorrect assembly of the myosin filament and microfilament, thereby affecting the synthetic and contractile functions of SMCs [ 10 , 11 ]. Pathogenic variants in MYH11 may result in hereditary TAAD/PDA, visceral myopathy 2, or megacystis–microcolon–intestinal hypoperistalsis syndrome [ 12 ]. The proliferation and migration of SMCs leads to the formation of intimal cushions in the ductus arteriosus after birth, and constriction of SMCs results in ductal contraction and permanent ductus closure [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%